Aksi “Mesiat” Pada Masayarakat Sasak Lombok Kajian Psikologi Sosial Tentang Harga Diri dan Perlawanan - Gazi Saloom (Schemata: Jurnal Pascasarjana UIN Mataram, 2021)
This paper aims to describe the “mesiat” behavior and its relationship with self-esteem in the Lombok Sasak community. This paper is a summary of the results of qualitative research on the cultural psychology of Lombok. Data was collected through social media interviews, especially WA with 3 sources of Sasak traditional stakeholders and religious leaders who understand Sasak customs. Data were analyzed using qualitative techniques, namely thematic analysis techniques with social psychology and cultural psychology theoretical approaches. Research findings suggest that cheating or messing around is done with the motive of defending personal self-esteem and group self-esteem. Begelepuk is done because of deliberate factors, namely fighting to show martial skills or an accidental factor, namely to defend oneself from other people's attacks. Keywords: Mesiat, self-esteem, tradition, sasak, culture Tulisan ini bertujuan menguraikan perilaku “mesiat” dan hubungannya dengan harga diri dalam masyarakat Sasak Lombok. Tulisan ini merupakan rangkuman dari hasil riset kualitatif tentang psikologi budaya Lombok. Data dikumpulkan melalui wawancara media sosial terutama WA dengan 3 narasumber pemangku adat Sasak dan tokoh agama yang faham adat Sasak. Data dianalisis dengan tehnik kualitatif yaitu tehnik analisis tematik dengan pendekatan teoritis psikologi sosial dan psikologi budaya. Temuan riset menyebutkan bahwa begelepuk atau mesiat dilakukan dengan motif membela harga diri pribadi dan harga diri kelompok. Begelepuk dilakuka karena faktor kesengajaan yaitu perang tanding untuk menunjukkan keahlian bela diri atau faktor tidaksengaja yaitu untuk membela diri dari serangan orang lain. Kata Kunci: Begelepuk, harga diri, tradisi, sasak , budaya